2019
DOI: 10.2217/cer-2018-0114
|View full text |Cite
|
Sign up to set email alerts
|

Complications and associated healthcare costs of transvenous cardiac pacemakers in Germany

Abstract: Aim: This study evaluated the occurrence and associated costs of pacemaker complications in Germany from 2010 to 2013. Patients & methods: Patients with a de novo or replacement implantation of a single or dual chamber pacemaker between 2010 and 2013 were followed for 12 months post-implant using German health insurance claims data. A case–control analysis was performed using propensity score matching to estimate the costs of complications. Results: Out of 12,922 implanted patients, 12.0% had a complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Complications arising after AVNA and pace represent a significant burden for the patient's quality of life and the healthcare system, generating substantial additional costs. Although, to the best of our knowledge, no study has explicitly focused on the long-term economic impact of AVNA and pace, two recent European studies have investigated the complications and associated healthcare costs after transvenous permanent pacemaker implantation in France [10] and Germany [11]. They have prospected an average additional cost at three years of around €6600 and €4600 respectively to manage the cardiac electronic devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications arising after AVNA and pace represent a significant burden for the patient's quality of life and the healthcare system, generating substantial additional costs. Although, to the best of our knowledge, no study has explicitly focused on the long-term economic impact of AVNA and pace, two recent European studies have investigated the complications and associated healthcare costs after transvenous permanent pacemaker implantation in France [10] and Germany [11]. They have prospected an average additional cost at three years of around €6600 and €4600 respectively to manage the cardiac electronic devices.…”
Section: Discussionmentioning
confidence: 99%
“…Leave-one-out analysis of outcomes to test for heterogeneity did not show significant change of the results (Supplementary Figs. [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Meta-analysismentioning
confidence: 99%
“…Given this background and the knowledge that device complications are common and device infections require complete system removal 23 both generating substantial healthcare costs, 24 novel strategies for the prevention of CIED infection are urgently needed. This section gives an overview of recommended strategies for preventing CIED infections in line with recent EHRA international consensus document on how to prevent, diagnose, and treat CIED infections.…”
Section: Introductionmentioning
confidence: 99%
“…Pacemaker implantation is a standard and safe therapeutic strategy for patients of all ages with bradyarrhythmia. Various complications associated with pacemaker implantation are common, but late-onset pacemaker-related pleural effusion is rarely reported [ 1 ]. Recently, Xiong et al reported 6 consecutive elderly patients with pleural effusion who had undergone a new pacemaker implantation and evaluated the clinical characteristics and therapeutic courses of pleural effusion [ 2 ].…”
Section: Introductionmentioning
confidence: 99%